2019
DOI: 10.1371/journal.pone.0211042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of elastic lumbar support belts on trunk muscle function in patients with non-specific acute lumbar back pain

Abstract: BackgroundA well-known supportive treatment for acute nonspecific back pain, elastic back support belts, are valued for their ability to accelerate natural self-healing, but there are concerns of a deconditioning effect due to their reliance on passive stabilization.MethodsTo evaluate the systematic effects of elastic abdominal belts on the trunk musculature, a total of 36 persons with acute lumbar back pain (no longer than one week) were divided into two groups: an abdominal belt wearing group (B) and a non-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…Regarding low back pain, different study protocols reported a positive effect of lumbar orthosis in 115 patients [2,6,18,21]. In contrast, four different randomized studies did not provide any pain relief after six months observation of 266 patients [8,14,17,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding low back pain, different study protocols reported a positive effect of lumbar orthosis in 115 patients [2,6,18,21]. In contrast, four different randomized studies did not provide any pain relief after six months observation of 266 patients [8,14,17,30].…”
Section: Discussionmentioning
confidence: 99%
“…All meta-analyses and literature research reviewed did not provide medical or technical differentiation [1,6,8,[11][12][13][14][15][16][17][18][19]24,26,27]. Thus, general orthotic designations such as "lumbar support" are used in the following.…”
Section: Overview Of the Current Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Because of the external support and the rigidity of the maternity support garments, the joint laxity decreases and stability increases. The use of maternity support garments should be advised to women with a higher risk of falling and for shorter periods as regular use of maternity support belts lower the activation of some trunk muscles [56].…”
Section: Discussionmentioning
confidence: 99%
“…Dadurch waren wir in der Lage, applikationsbedingte von krankheitsbedingten Einflüssen zu trennen. Beide Studien wurden bereits publiziert und sollen hier hinsichtlich der verallgemeinerbaren Befunde zusammengefasst werden [2] [9].…”
unclassified